qEEG: Its utility in the psychiatric clinical practice - Teixeira, João Marques (2015)
The use of auxiliary diagnostic means in psychiatry is an old problematic issue, mainly because the nature of the process of becoming mentally ill, together with the conceptual approach that has being used to explain it. The recent technological advances, mainly in the neuroimage techniques, have come to increase the hope of using the knowledge acquired by those studies in the psychiatric clinical practice. However, that hope vanished quickly. In this paper, the author analyzes the putative reasons to explain that failure, proposing at the same time the reasons and the evidence that sustain the clinical use of another technology – the quantitative electroencephalography (qEEG) – using several clinical cases to illustrate the use of qEEG in different clinical situations.